Synthesis, characterisation and biological evaluation of phosphinegold(I) thiolates / Yeo Chien Ing - Yeo, Chien Ing (2016)
A series of mononuclear phosphanegold(I) thiocarbamides, Ph3PAu{SC(OR)=NC6H4X-4} for R = alkyl, X = H, CH3, Cl and NO2, and dinuclear (Ph2P-Fc-PPh2){AuSC(OiPr)=NC6H4X-4}2 and (R3PAu)2{1,4-[SC(OMe)=N]2C6H4} with X = H, CH3, Cl and iPr, R = Et, Ph and Cy, were prepared from the reaction of the respective phosphanegold(I) precursor with thiolate ligands in the presence of base. The complexes were characterised by IR spectroscopy, (multi)NMR spectroscopy, elemental analyses, thermogravimetric analyses, UV/Vis spectroscopy, photoluminescent study, powder X-Ray diffraction (PXRD) analyses and single-crystal X-ray diffraction studies. The crystal structures of the compounds featured essentially linear gold atom coordination geometries defined by phosphane-P and thiolate-S atoms. Both parent phosphanegold(I) complexes and the N-bound p-tolyl derivatives showed promising cytotoxicity against the HT-29 cancer cell line, and the N-bound p-tolyl series were found to exhibit specific antibacterial activity against Gram-positive bacteria. Dinuclear compounds, (Ph2P-Fc-PPh2){AuSC(OiPr)=NC6H4X-4}2, possessed better cytotoxicity against HEK-293 embryonic kidney cells as compared to the mononuclear analogues and less toxic against MCF-7 breast cancer cell lines. (R3PAu)2{1,4-[SC(OMe)=N]2C6H4} displayed unexpected Au…π interactions which are more stable by at least 12 kcal mol-1. The disk diffusion results for this series demonstrated that the Et3P analogue exhibited a broad spectrum of anti-bacterial activity toward 24 strains of Gram-positive and Gram-negative bacteria while the Ph3P and Cy3P analogues were limited to Gram-positive bacteria. Contemplating the study on phosphanegold(I) complexes, exploration studies conducted on (Ph3P)2Cu[ROC(=S)N(H)Ph]Cl with R = Me, Et and iPr revealed interesting interactions, i.e. C–H···π(quasichelate ring) where a six-membered quasi-chelate ring is closed by an N–H···Cl hydrogen bond. Calculations suggest that the energy of attraction provided by such interactions approximates 3.5 kcal mol-1.